Amyloid beta peptides in human plasma and tissues and their significance for Alzheimer's disease - Roher, Alex E; Esh, Chera L; Kokjohn, Tyler A; Castaño, Eduardo M; Van Vickle, Gregory D; Kalback, Walter M; Patton, R. Lyle; Luehrs, Dean C; Daugs, Ian D; Kuo, Yu-Min; Emmerling, Mark R; Soares, Holly; et al. (Alzheimer's & dementia, 2009)
Abstract Background We evaluated the amounts of amyloid beta (Aβ)) peptides in the central nervous system (CNS) and in reservoirs outside the CNS and their potential impact on Aβ plasma levels and Alzheimer's disease (AD) pathology. Methods Amyloid β levels were measured in (1) the plasma of AD and nondemented (ND) controls in a longitudinal study, (2) the plasma of a cohort of AD patients receiving a cholinesterase inhibitor, and (3) the skeletal muscle, liver, aorta, platelets, leptomeningeal arteries, and in gray and white matter of AD and ND control subjects. Results Plasma Aβ levels fluctuated over time and among individuals, suggesting continuous contributions from brain and peripheral tissues and associations with reactive circulating proteins. Arteries with atherosclerosis had larger amounts of Aβ40 than disease-free vessels. Inactivated platelets contained more Aβ peptides than activated ones. Substantially more Aβ was present in liver samples from ND patients. Overall, AD brain and skeletal muscle contained increased levels of Aβ. Conclusions Efforts to use plasma levels of Aβ peptides as AD biomarkers or disease-staging scales have failed. Peripheral tissues might contribute to both the circulating amyloid pool and AD pathology within the brain and its vasculature. The wide spread of plasma Aβ values is also due in part to the ability of Aβ to bind to a variety of plasma and membrane proteins. Sources outside the CNS must be accounted for because pharmacologic interventions to reduce cerebral amyloid are assessed by monitoring Aβ plasma levels. Furthermore, the long-range impact of Aβ immunotherapy on peripheral Aβ sources should also be considered.